Lasers in Dermatology and Medicine - Nouri, Keyvan; SpringerLink (Online service) (London : Springer London, 2012)
Laser technology is quickly evolving with developments in laser technology and new indications in their use. Laser medicine has become a major discipline in its own right, with applications in dermatology, plastic surgery, ophthalmology, cardiology, gynecology, otolaryngology, neurology and neurosurgery. Lasers in Dermatology and Medicine offers a comprehensive review of all the major disciplines in medicine in which lasers are being used and has been written by a host of well-known authors in their respective fields. Each has covered their topic in the most comprehensive, readable, and understandable format, giving the reader a practical understanding of the various topics on lasers and how lessons learnt in one discipline can go on to benefit other uses. This book has been written to serve as a cornerstone of laser usage in medicine, ultimately leading to better patient care and treatments. It will therefore be of considerable interest to all physicians who use or are interested in using lasers in their practice from dermatologists and plastic surgeons to ophthalmologists, cardiologists, gynecologists, otolaryngologists, neurologists and others.
Keywords: Medicine; Dentistry; Dermatology; Gynecology; Ophthalmology; Head -- Surgery; Medicine & Public Health; Dermatology; Ophthalmology; Head and Neck Surgery; Gynecology; Dentistry